O pós FUNDEB no oferecimento de matrículas para a educação infantil no estado de São Paulo - Abdalla, Patrícia Adriana [UNESP] (2015)
This work aims to study the partnerships made by cities between the public and private sectors to educational offering in early childhood education, identifying and analyzing the implications of FUNDEB for this age group, analyzing the growth of public and contracted enrollment in São Paulo counties during the period of 2008 and 2013. After the establishment of the LDB, public resources are intended to meet the public schools, and may also be allocated to community, religious or philanthropic schools that declare non-profit making. In 1996, it was approved the creation of FUNDEF, that with the prioritization of basic education as their financing, leaves the childhood education in the background. However, in 2007, the Fund was replaced by FUNDEB, which regards the appreciation of the childhood education, thus ensuring its funding. For this research, methods of qualitative research of bibliographic and documentary approach are used. As a result, when it comes to childcare, growth occurs in both public sector and private sector. In preschool there are almost no new agreements from 2009 onwards, and in almost all cities the number of public enrollment is greater than the contracted enrollment. These results indicate stabilization in the number of cities with agreements, and concentration of advancement and increase in contracted enrollments in large, very large, metropolitan cities, with greater intensity in day care centers